A web application development project II - Chew, Derwin Sheng Yuan. (2012)
This Final Year Project report details the development of a web based scaffolding dynamic system for problem representation (PRES-on). The concept of conceptual change has prompt researchers to come out with different approaches in order to achieve significant changes in learning and instructional approach that are suggested to induce conceptual change will be introduced.